1998
DOI: 10.1001/archneur.55.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy Trends in the Patterns and Outcomes of Care at Academic Medical Centers, 1990 Through 1995

Abstract: Despite dramatic changes that have occurred in patient characteristics and in hospital management practices for patients undergoing a carotid endarterectomy from 1990 to 1995, we were unable to detect any measurable impact on patient outcomes. These data have implications for monitoring and evaluating the impact of systemwide change on the overall quality of care for patients undergoing a carotid endarterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
(82 reference statements)
0
13
1
Order By: Relevance
“…A recent study from 10 academic medical centers for the period 1990 to 1995 by Holloway et al 27 found an inhospital mortality rate of only 0.5% for principal procedure CEAs, which is even lower than the rate of 0.9% obtained nationally for principal procedure CEAs from all types of hospitals in this study. A recent study from 10 academic medical centers for the period 1990 to 1995 by Holloway et al 27 found an inhospital mortality rate of only 0.5% for principal procedure CEAs, which is even lower than the rate of 0.9% obtained nationally for principal procedure CEAs from all types of hospitals in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…A recent study from 10 academic medical centers for the period 1990 to 1995 by Holloway et al 27 found an inhospital mortality rate of only 0.5% for principal procedure CEAs, which is even lower than the rate of 0.9% obtained nationally for principal procedure CEAs from all types of hospitals in this study. A recent study from 10 academic medical centers for the period 1990 to 1995 by Holloway et al 27 found an inhospital mortality rate of only 0.5% for principal procedure CEAs, which is even lower than the rate of 0.9% obtained nationally for principal procedure CEAs from all types of hospitals in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…Furthermore, the reported mean postoperative LOS after CEA has significantly decreased in numerous practice settings. 9,12,[23][24][25][26][27][28][29][30][31] Unlike other institutions, 12,29 we did not observe a linear trend in LOS over time.…”
Section: Discussionmentioning
confidence: 74%
“…Among preoperative risk factors, we found female gender and history of CHF or COPD to be predictive of ELOS in accordance with prior literature suggesting a gender difference in outcomes after CEA [7][8][9][10] and worse outcomes after carotid revascularization in patients with heart failure or COPD. [11][12][13][14] Women in our cohort had median postoperative LOS 1 day longer than men (P < .01) and had 1.9 times the odds of ELOS compared with men. Patients with either CHF or COPD had approximately twofold odds of ELOS, even after adjusting for other factors.…”
Section: Discussionmentioning
confidence: 89%
“…Previously reported 30-day readmission rates after CEA range from 0% to 9.2%. [5][6][7][8][9][10][11] The largest of these studies 6 was a retrospective evaluation of 7019 CEAs at multiple centers between 1990 and 1995. Readmission rates at included centers Our observed overall perioperative complication rate of 9.9% is within the range reported in the literature.…”
Section: Discussionmentioning
confidence: 99%